Gramsci and the state - Buci-Glucksmann, Christine; Fernbach, David (London : Lawrence and Wishart, 1980)
Bibliotheek François Vercammen
Oorspronkelijke titel: Gramsci et l'état
Engels
Monografie
Keywords: Gramsci, Antonio